Peningkatan Kemandirian dan Hasil Belajar Tematik melalui Project Based Learning - Swastantika Kumala Devi; Bambang Ismanto; Firosalia Kristin (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of this study was to describe the implementation of the steps of the project based learning model in increasing the independence and learning outcomes of grade IV students of SD 2 Blotongan. This study uses two cycles, each cycle has procedures including planning, action, observation and reflection. Qualitative data analysis techniques in the form of independent data analysis and quantitative data in the form of data analysis of completeness of learning. The results of this study indicate the application of project based learning learning models can improve the independence and thematic learning outcomes. This is indicated by an increase in student learning independence in the pre-cycle by 50%, cycle 1 by 85% and cycle II by 100%. This resulted in learning completeness which increased to 85%